High‐resolution manometry and swallow outcomes after vocal fold injection medialization for unilateral vocal fold paralysis/paresis. Issue 7 (27th February 2019) - Kammer, Rachael E.; Jones, Corinne A.; Johnson, Aaron M.; Dailey, Seth H.; McCulloch, Timothy M.; Thibeault, Susan L.
Abstract: Background: Injection medialization is performed to improve glottic closure, thereby airway protection. Overall objective to determine if unilateral injection medialization changes glottal area with concomitant adjustments in penetration/aspiration scale (PAS) scores and pharyngeal high‐resolution manometry (HRM) parameters. Methods: Enrolled 17 adults with unilateral vocal fold paralysis/paresis and aspiration/penetration. Fiberoptic endoscopic evaluation of swallowing and pharyngeal HRM completed at (1) baseline (within 1 week before injection), (2) postinjection (within 1 week post injection), and (3) 1‐month postinjection. Comparisons between time points for PAS scores, glottal area, pharyngeal pressure, and timing. Results: No significant differences in normalized glottal area. No significant differences in PAS scores, for any consistency. Significantly increased rate of mesopharynx pressure rise and maximum pressure at 1 month postinjection ( P  = .01 and .02, respectively) compared to baseline. Significant decrease in mesopharynx integral from baseline to 1 week postoperative ( P  = .03). Conclusion: Findings suggest unilateral vocal fold injection medialization had limited effect on swallow function.